2022
DOI: 10.17219/dmp/143544
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination on the inner surface of the masks used by clinicians in a dental clinic

Abstract: Background.Wearing masks has become an essential safety measure during the coronavirus 2019 (COVID-19) pandemic. Especially clinicians in dental clinics should focus on infection control. However, there is currently no data regarding the frequency of replacement of the masks used in hospitals. Hence, it is necessary for dental clinic staff, who deal with many patients in an aerosol-producing environment, to have precise mask-wearing guidelines.Objectives. The aim of this study was to evaluate the contamination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…In a previous study, the contamination rate inside the mask was also affected by wearing time and conversation, perhaps due to increased saliva outflow (Lee, 2022). In addition, previous studies showed that mastication could cause saliva outflow (Gavião et al, 2004).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In a previous study, the contamination rate inside the mask was also affected by wearing time and conversation, perhaps due to increased saliva outflow (Lee, 2022). In addition, previous studies showed that mastication could cause saliva outflow (Gavião et al, 2004).…”
Section: Resultsmentioning
confidence: 92%
“…The oral cavity contains many nutrients (Cha, 2021). It has been reported that wearing a mask maintains a warm temperature and high humidity inside the mask (Lee, 2022). Therefore, the inside of a mask presents ideal conditions for bacterial growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, bacterial colonization on food packaging can decrease the food’s shelf-life or spread foodborne diseases [ 23 ]. Additionally, bacterial contamination also occurs on the inner and outer parts of face masks [ 24 , 25 ]. Since PLA is sensitive to all available sterilizing methods [ 26 ] and can become easily contaminated after sterilization, antibacterial components are frequently added to it.…”
Section: Introductionmentioning
confidence: 99%
“…3 Hence, in our previous study, we evaluated the temperature, humidity and contamination rates on the inner layer of masks according to the mask-wearing time. 4 Yet, it is important to assess the contamination rates on the outer layer of masks used in dentistry as well. No studies have referred to this issue so far.…”
Section: Introductionmentioning
confidence: 99%